Radicals and rational eqns: How are k=-2,-3 the soln's to (K+2)(k+3)=0?

(K+2)(k+3)=0

How are the possible solutions k=-2 and k=-3
K is a place holder for a number. Since k is just a number (not known yet but still a number), then k+2 is just a number. Likewise k+3 is just a number We know that when we multiply these two numbers (k=2 and k+3) we get 0.

Well if you multiply two numbers and get 0, then one or both of the numbers must be 0.

So when is k+2 =0 since -2 + 2 = 0 we have k=-2

When is k+3 = 0? Since -3 + 3 = 0, it follows that k= -3

What were you getting when you plugged in k= -2 into the equation? What did you get when you plugged in k = -3 into the equation?
 
They are in Khan i left them out b/c I thought they were unnecessary given the title description above
 
They are in Khan i left them out b/c I thought they were unnecessary given the title description above
So there are radicals? So is the radical the 2nd root or the 3rd root or is it the 1/3 root, all of the above or something else? Is the unknown radical on the k or k+2 or 2 or k+3, ...? Since this is rational expression where is the division sign. Is it between .....? How are we suppose to know? Why not just simply write the exact problem?
 
Top